A High‐performance Lithium Metal Battery with a Multilayer Hybrid Electrolyte. Issue 1 (3rd March 2022) - Yi, Qiang; Zhang, Wenqiang; Wang, Tianyuan; Han, Junxing; Sun, Chunwen
Abstract : Solid‐state batteries have been considered as a good choice for substituting traditional batteries with liquid electrolytes because of their high energy density and safe property. However, a little amount of flammable non‐aqueous liquid electrolyte or polymer electrolyte is usually required to improve the interfacial contact, which is adverse to safety. Here, a nonflammable gel is prepared by hydrogen‐bond interaction and applied as an interfacial layer to improve the performance of solid‐state batteries. The prepared multilayer hybrid electrolyte (MHE) composed of gel and CPE shows a wide electrochemical window (5.3 V vs Li/Li + ), high ionic transference number (0.57), and ionic conductivity (7.18 × 10 −4  S cm −1 ) at room temperature. Thus, the assembled Li symmetric cell with MHE can cycle over 650 h at 0.5 mA cm −2 with a lower overpotential of ~61 mV. The LiFePO4 |MHE|Li cell exhibits a higher discharge capacity of 107.8 mAh g −1 even cycled at 5 C. It also shows superior capacity retention of 96.4% after 1000 cycles at 0.5 C. This work provides a promising strategy for designing high‐performance solid‐state batteries. Abstract : A nonflammable gel is prepared by hydrogen‐bond interaction and applied as an interfacial layer to improve the performance of solid‐state batteries. The prepared multilayer hybrid electrolyte (MHE) composed of gel and CPE shows wide electrochemical window, high ionic transference number, and ionic conductivity at room temperature. The LiFePO4 |MHE|Li cell exhibits remarkable rate capability and cycling performances.